Tinjauan Hukum Ekonomi Syari’ah: Take Over Pembiayaan Mikro Bank Syari’ah - Nurasikin, Akhmad; Handayani, Tri; Rahman, Arif; Fatmawati, Siti Selviyah (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2021)
Although Indonesia is still facing formidable challenges due to the Covid-19 pandemic, the distribution of financing in the MSME sector and the micro segment continues to increase. "This shows that BSI continues to support the growth of MSMEs in the midst of the pandemic storm. Until June 2021, MSME financing at BSI was recorded at 36.82 trillion rupiah. Therefore, the authors are interested in conducting research with the title "Review of Islamic Economic Law Take Over Sharia Bank Microfinance". The purpose of this study is to analyze the TO process of microfinance in Islamic banks and its legal review. The research method used is descriptive analytical while the approach uses empirical juridical and data collection by literature study, interviews and observations. The results of the study stated the views of several scholars and sharia economists regarding the Qardh wal Murabahah contract used as a permissible contract, but in practice it must be subject to strict supervision. The Micro Financing Take Over process is guided by the DSN-MUI Fatwa Number: 31/DSN-MUI/VI/2002 concerning Debt Transfer (Alternative 1) and has become a positive law through Bank Indonesia Regulations (PBI). The legal consequence of this Qardh wal Murabahah contract is that the right of the first customer as a guarantee right holder is legally transferred to the new customer as stated in the Mortgage Certificate (SHT) and Fiduciary Guarantee Certificate.Walaupun Indonesia masih menghadapi tantangan yang berat akibat pandemi Covid-19, namun penyaluran pembiayaan di  sektor UMKM dan segmen mikro terus meningkat. “Ini menunjukkan BSI terus mendukung pertumbuhan UMKM di tengah badai pandemi. Hingga Juni 2021, pembiayaan UMKM di BSI tercatat sebesar 36,82 triliun rupiah. Oleh karena itu penulis tertarik melakukan penelitian dengan judul ”Tinjauan Hukum Ekonomi Syariah Take Over Pembiayaan Mikro Bank Syari’ah”. Tujuan penelitian ini ialah untuk menganalisis proses TO pembiayaan mikro di bank syari’ah dan tinjauan hukumnya, Adapun Metode penelitian yang digunakan bersifat deskriptif analitis sedangkan pendekatannya menggunakan yuridis empiris dan pengumpulan data dengan studi kepustakaan, wawancara dan observasi. Hasil penelitian tersebut menyatakan pandangan beberapa ulama’ dan pakar ekonomi syari’ah mengenai akad Qardh wal Murabahah yang digunakan merupakan akad yang dibolehkan, namun dalam praktiknya harus mendapat pengawasan yang ketat. Proses Take Over Pembiayaan Mikro berpedoman pada Fatwa DSN-MUI Nomor: 31/DSN-MUI/VI/2002 tentang Pengalihan Utang (Alternatif 1) dan menjadi hukum positif melalui Peraturan Bank Indonesia (PBI). Akibat hukum dari akad Qardh wal Murabahah ini ialah hak nasabah pertama sebagai pemegang hak jaminan beralih secara hukum kepada pihak nasabah baru yang tertuang dalam Sertifikat Hak Tanggungan (SHT) dan Sertifikat jaminan Fidusia.